2000
DOI: 10.1143/jjap.39.5465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crystallization Annealing Sequence for SrBi2Ta2O9 (SBT) Film on Pt/SBT Interface Morphology and Electrical Properties of Ferroelectric Capacitor

Abstract: SrBi2Ta2O9 (SBT) film was crystallized to form fine grains and a smooth surface by rapid thermal annealing (RTA), but form large grains and a rough surface by main furnace annealing. The sequence of furnace annealing was changed to improve the morphology of the Pt/SBT interface and the leakage property of a Pt/SBT/Pt capacitor. For the conventional sequence of furnace annealing before top electrode deposition, the capacitor showed a good switching polarization (P*-P∧) of 17 µC/cm2 but a high short fail rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In some cases, the effect of the electrode brings about modifications of the microstructure of the ferroelectric film and in some cases, the electrode directly controls the properties. [7][8][9] An SBT layer must be annealed in oxygen ambient after deposition. This immediately limits the choice of electrodes, particularly those for the bottom electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the effect of the electrode brings about modifications of the microstructure of the ferroelectric film and in some cases, the electrode directly controls the properties. [7][8][9] An SBT layer must be annealed in oxygen ambient after deposition. This immediately limits the choice of electrodes, particularly those for the bottom electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…11 Miura 12 and Yang et al 13 showed that the SBN phase was crystallized via a metastable fluoritelike phase in a cubic structure. In this system, stoichiometric deviations can occur, leading to intermediary pyrochlore and fluorite phases.…”
mentioning
confidence: 99%
“…On the other hand, it has been well known that traditional ferroelectric materials such as SrBi2Ta2O9 (SBT), Bi3.25La0.75Ti3O12 (BLT), and PbZr0.52TiO0.48O3 (PZT) are really attractive in electronic devices application. For instance, SBT thin films possess a low leakage current but a small remnant polarization and high crystallization temperature [8], PZT thin films have a large remnant ________ polarization and lower crystallization temperature, but a large leakage current [9,10]. As a trade-off material, BLT thin films involve a medium level of leakage current, remnant polarization and crystallization temperature between SBT and PZT thin films [11].…”
Section: Introduction mentioning
confidence: 99%